2022
DOI: 10.3390/jcm11195723
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of His Bundle Pacing Compared to Classic Resynchronization Therapy in Patients with Pacing-Induced Cardiomyopathy

Abstract: Pacing-induced cardiomyopathy (PICM) is among the most common right ventricular pacing complications. Upgrading to cardiac resynchronization therapy (CRT) is the recommended treatment option. Conduction system pacing with His bundle pacing (HBP) has the potential to restore synchronous ventricular activation and can be an alternative to biventricular pacing (BVP). Patients with PICM scheduled for a system upgrade to CRT were included in the prospective cohort study. Either HBP or BVP was used for CRT. Electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In the study of PICM, most scholars seemed to be only interested in the preoperative versus postoperative comparison of emerging physiological pacing (CRT, HBP, and LBBP). For example, Khurshid et al and Gardas et al respectively reported that CRT and HBP might improve left ventricular electrical and mechanical synchronization (5,20), and Ye et al and Qian et al also reported that LBBP upgrade was likely to improve the cardiac function and clinical outcomes of PICM patients (4,21). All the points mentioned above were consistent with the findings we derived.…”
Section: Discussionsupporting
confidence: 88%
“…In the study of PICM, most scholars seemed to be only interested in the preoperative versus postoperative comparison of emerging physiological pacing (CRT, HBP, and LBBP). For example, Khurshid et al and Gardas et al respectively reported that CRT and HBP might improve left ventricular electrical and mechanical synchronization (5,20), and Ye et al and Qian et al also reported that LBBP upgrade was likely to improve the cardiac function and clinical outcomes of PICM patients (4,21). All the points mentioned above were consistent with the findings we derived.…”
Section: Discussionsupporting
confidence: 88%
“…Another situation that LBBAP might be preferred to CRT is PICM as in our case. As we described before, a previous study observed that his bundle pacing was associated with a better improvement in LVEF than CRT in patients with PICM [12]. Although LBBAP is different from his bundle pacing, both target conduction system pacing, which is believed to be more physiologic than biventricular pacing.…”
Section: Discussionmentioning
confidence: 80%
“…The therapeutic effect of CRT among patients with PICM has also been shown by a recent meta-analysis [11]. There is a report that his bundle pacing might be more effective in improving LVEF than CRT among PICM patients [12]. However, it should be cautiously interpreted because the study has a limited cohort size and there was no guarantee that CRT was fully optimized.…”
Section: Discussionmentioning
confidence: 89%
“…and Gardas et al. respectively reported that CRT and HBP might improve left ventricular electrical and mechanical synchronization, 6,20 and Ye et al. and Qian et al.…”
Section: Discussionmentioning
confidence: 99%